Analisis Kandungan Mineral Tembaga (Cu) yang Terdapat pada Struktur Batu Tambang Dengan Metode Atomic Absorption Spectrofotometer (AAS) - Bukhari, Imam; Hayati, Susru Hiyatun; Humayroh, Nisa; Ahzan, Sukainil; Prasetya, Dwi Sabda Budi (Lensa : Jurnal Kependidikan Fisika, 2018)
[Title: Analysis of Copper (Cu) Mineral Content in the Mining Rock Structure using the Atomic Absorption Spectrophotometer (AAS) Method]. This research was conducted with the aim of: 1) Making chitosan based on local crab shells NTB, 2) Test the absorption of Au ions using chitosan with AAS. This research was carried out using the AAS method, namely by making chitosan from crab shells, Au stock solution which was prepared in the first stage was given chitosan powder and carried out absorption with varying times. Analysis of gold content in Au stocks that have been treated with AAS to determine the remaining Au content and Au absorbed.